2018
DOI: 10.3928/01484834-20180322-08
|View full text |Cite
|
Sign up to set email alerts
|

Stepping Into Their Shoes: The Ostomy Experience

Abstract: The structured reflective journaling yielded rich student learning data. Responses were evident of self-proclaimed change in attitudes, deeper understanding of the patient experience, and achievement of the learning objectives. [J Nurs Educ. 2018;57(4):233-236.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…Findings from focus groups were consistent with the response to questionnaires and students reported a more positive attitude towards those who are obese as a result of completing the simulation ( Hunter et al, 2018 ). Similarly, a study in which undergraduate nurses wore ostomy bags as part of a simulation activity reported that the simulation experience was an effective strategy to help student nurses relate to the reality and feelings of others ( Hood, Haskins & Roberson, 2018 ). Trained actors have also reported the power of experiencing a patient's perspective through acting in the role of those with chronic illness ( Jarosinski & Webster, 2016 ).…”
Section: Introductionsupporting
confidence: 64%
“…Findings from focus groups were consistent with the response to questionnaires and students reported a more positive attitude towards those who are obese as a result of completing the simulation ( Hunter et al, 2018 ). Similarly, a study in which undergraduate nurses wore ostomy bags as part of a simulation activity reported that the simulation experience was an effective strategy to help student nurses relate to the reality and feelings of others ( Hood, Haskins & Roberson, 2018 ). Trained actors have also reported the power of experiencing a patient's perspective through acting in the role of those with chronic illness ( Jarosinski & Webster, 2016 ).…”
Section: Introductionsupporting
confidence: 64%